Discover Public Health - Tam, Clarence; Coughlin, Steven S.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Discover Public Health is a fully open access, peer-reviewed journal that supports multidisciplinary research and policy developments across all fields relevant to public health and societal impacts related to this. The journal aims to be an international resource for researchers, policy makers and the general public for recent advances in public health, and its uses in research development and society. As a fully open access journal, we ensure that our research is highly discoverable and instantly available globally to everyone. The journal particularly welcomes work that aims to address the United Nations Sustainable Development Goals, especially No Poverty; Zero Hunger, Good Health and Well-Being; Gender Equality. Topics Topics welcomed at Discover Public Health include but are not limited to the following: Epidemiology and biostatistics Disease surveillance, outbreak analysis, health metrics, risk assessment, disease modeling, statistical inference, data analysis, public health surveillance, predictive modeling, health trends Environmental and occupational health Environmental exposures, workplace safety, hazard assessment, pollution studies, toxicology, ergonomics, environmental health assessments, risk management, sustainable health. Global health Cross-border health issues, international cooperation, health equity, disease eradication, global health initiatives, international health regulations, health diplomacy, world health trends. Health promotion and disease prevention Wellness, proactive interventions, preventive measures, lifestyle, vaccination, screening, health campaigns, risk reduction, community engagement, health literacy. Health policy and management Health governance, policy analysis, health systems, healthcare administration, resource allocation, public health law, regulatory affairs, strategic planning, health services. Social and behavioral sciences Health psychology, behavior change, social determinants, community dynamics, health beliefs, cultural health, health interventions, societal impact, behavior modeling. Health education and communication Health literacy, awareness campaigns, health communication strategies, patient education, community outreach, health information dissemination, behavior change communication, media and health. Maternal and child health Prenatal care, child nutrition, reproductive rights, maternal mortality, child health initiatives, birth outcomes, lactation support, family health, developmental health Health technology and informatics Health IT, electronic health records, data analytics, digital health, telemedicine, health apps, medical databases, informatics in research, health data security. Content types Discover Public Health welcomes full-length Research articles as well as Brief Communications of empirical findings, Reviews, Perspectives, Comments, Case Studies, Registered Reports, and Data Notes from across the full range of disciplines concerned with public health. The journal also publishes guest-edited Topical Collections of relevance to all aspects of public health and its applications. For more information, please follow up with our journal publishing contact.
Keywords: Epidemiology; Public health; Sociology$1 (BMethodology.s; Biometry; Epidemiology; Public Health; Sociological Methods; Biostatistics